Pembinaan Kepemimpinan Pendidikan Unggul Di Era Revolusi Industri 4.0 dan Society 5.0 di Growing Hope Lampung - Dreitsohn Franklyn Purba; Asep Suryana; Djam'an Satori; Diding Nurdin; Sunarto Sunarto; Robi Prianto; Yohanes Hasiholan Tampubolon (Indonesian Journal of Community Services in Engineering & Education (IJOCSEE), 2023)
The challenges faced by educators and professionals in the education sector, particularly during the Industrial Revolution 4.0 and Society 5.0 eras, require them to expand their knowledge and update their skills to keep up with the rapid changes. In response to this need, coaching sessions were conducted at the Harapan Masa Depan Foundation in Lampung. The approach involved visiting Growing Hope Lampung, where guidance and training were provided to the teachers and therapists of the foundation. This training aimed to raise awareness and enhance the understanding of the community, especially regarding the changes brought about by technological advancements and social transformations in the field of education during the Industrial Revolution 4.0 and Society 5.0. By equipping them with relevant knowledge and skills, this initiative helps prepare educators and professionals for future challenges and opportunities in the evolving educational landscape.